The Influence of Human Capital and Welfare on the Quality of Democracy in Indonesia - Saukani, Mohd Nasir Mohd; Nurdin, Iing; Aji, Rizqon Halal Syah (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:Indonesia is the third-largest democratic nation in the world. Democracy is viewed as a constitutional structure capable of achieving human progress, since political rights, civil liberties and the State's responsibility for achieving human development reside in a democratic system. The objectives of this analysis are, firstly, to describe and analyze the state of democracy in Indonesia using indicators of the democracy index (political rights, civil rights, and democratic institutions); secondly, to explain and analyze the basis, policy, execution of democracy and human development; and, thirdly, to evaluate and analyze basic decisions and policies through indicators of human rights and human development. This research uses qualitative approaches based on primary data and secondary data (literature review) but also accompanied by quantitative data and triangulation analysis techniques. The findings of the study indicate that, firstly, Indonesia has largely developed a stable political structure, although there is still a great deal of frustration with the weak capability of democratic institutions. Democracy in Indonesia is still marked by unethical behavior; secondly, Indonesia's democracy continues to step forward, yet still places Indonesia in the category of procedural democracy, not yet in the category of substantive democracy; thirdly, there is a clear and constructive relationship, but not explicitly and steadily, between democracy and human progress, especially human development. The implication is that numerous ideas and arguments can be confirmed that democracy can foster human development; while Indonesia cannot yet be classified as a truly democratic country as a condition for being a welfare state.Keywords: Democracy, Renewal, Welfare, Human Development.AbstrakIndonesia adalah negara demokrasi ketiga terbesar di dunia. Demokrasi dilihat sebagai sistem politik yang mampu merealisasikan pembangunan manusia, karena dalam sistem demokrasi terdapat hak politik, kebebasan civil dan tanggungjawab negara untuk merealisasikan pembangunan manusia. Tujuan kajian ini yaitu, pertama, untuk menjelaskan dan menganalisis keadaan demokrasi di Indonesia dengan menggunakan penunjuk indeks demokrasi (hak politik, hak-hak civil dan institusi demokrasi); kedua, menjelaskan dan menganalisis dasar, strategi, pelaksanaan yang berkaitan dengan demokrasi dan pembangunan manusia; ketiga, menilai dan menganalisis keputusan dasar dan strategi melalui penunjuk indeks pembangunan manusia (pendidikan, kesehatan, kehidupan yang layak) serta menganalisis hubungan antara demokrasi dan pembangunan manusia di Indonesia. Kajian ini menggunakan kaedah kualitatif berdasarkan data primer, dan data sekunder (kajian literatur) turut didukung oleh data kuantitatif serta teknik analisis triangulasi. Hasil kajian menunjukkan bahwa; pertama, Indonesia pada umumnya telah mengukuhkan sistem politik demokratis, walaupun masih banyak ketidakpuasan terhadap kemampuan institusi demokratik yang lemah. Demokrasi di Indonesia juga bercirikan oleh perilaku korupsi; Kedua, demokrasi Indonesia cenderung bergerak ke depan, tetapi masih terus memposisikan Indonesia dalam kategori demokrasi prosedur, belum mencapai kategori demokrasi substantif; Ketiga, ada hubungan yang signifikan dan positif walaupun tidak secara langsung dan lambat antara demokrasi dan pembangunan manusia, yaitu melalui kenaikan indeks pendidikan, indeks kesehatan, indeks kuasa beli. Implikasinya adalah dapat disahkan pelbagai teori dan alasan bahwa demokrasi dapat menggalakkan pembangunan manusia; walaupun Indonesia belum dapat dikategorikan sebagai negara demokrasi seutuhnya sebagai syarat untuk menjadi negara kesejahteraan.Kata Kunci: Demokrasi, Pembaharuan, Kesejahteraan, Pembangunan manusiaАннотация:Индонезия - третья по величине демократическая страна в мире. Демократия рассматривается как конституционная структура, способная обеспечить прогресс человечества, поскольку политические права, гражданские свободы и ответственность государства за достижение человеческого развития присущи демократической системе. Цели этого анализа: во-первых, описать и проанализировать состояние демократии в Индонезии с использованием показателей индекса демократии (политические права, гражданские права и демократические институты); во-вторых, объяснять и анализировать основы, политику, реализацию демократии и человеческого развития; и, в-третьих, для оценки и анализа основных решений и политики с помощью показателей прав человека и человеческого развития. В этом исследовании используются качественные подходы, основанные на первичных и вторичных данных (обзор литературы), но также сопровождаемые количественными данными и методами триангуляционного анализа. Результаты исследования показывают, что, во-первых, в Индонезии в значительной степени сложилась стабильная политическая структура, хотя по-прежнему существует большое разочарование по поводу слабости демократических институтов. Демократия в Индонезии по-прежнему отличается неэтичным поведением; во-вторых, демократия Индонезии продолжает шагать вперед, но все же относит Индонезию к категории процедурной демократии, но не к категории реальной демократии; в-третьих, существует четкая и конструктивная связь между демократией и человеческим прогрессом, особенно человеческим развитием, но не однозначно и устойчиво. Подразумевается, что можно подтвердить многочисленные идеи и аргументы о том, что демократия может способствовать человеческому развитию; в то время как Индонезия еще не может быть классифицирована как истинно демократическая страна как условие существования государства всеобщего благосостояния.Ключевые слова: демократия, обновление, благосостояние, человеческое развитие.